FRI0365 REAL-WORLD EFFECTIVENESS AND SAFETY OF APREMILAST IN A LARGE COHORT OF GERMAN PATIENTS WITH PSORIATIC ARTHRITIS: 1-YEAR ANALYSIS OF AN ONGOING MULTICENTER, PROSPECTIVE, NON-INTERVENTIONAL STUDY. (2nd June 2020) - Wollenhaupt, J.; Strothmeyer, H.; Fiene, M.; Morys, S.; Bach, C.; Roemmler-Zehrer, J.
Abstract : Background: Apremilast (APR) has been studied extensively in phase III randomized, controlled trials. However, real-world information is limited on the effectiveness and safety of APR in patients with psoriatic arthritis (PsA). Objectives: To assess the effectiveness and safety of APR in a large cohort of patients with active PsA from routine clinical practice settings in Germany. Methods: In this multicenter, prospective, non-interventional study, the primary endpoint was the proportion of patients reaching ≥1 point (≥20%) improvement from baseline (BL) in the Physician's Global Assessment of Disease Activity (PhGA) score. Other endpoints included effects on swollen and tender joint counts (SJC/TJC), psoriasis-involved body surface area (BSA), enthesitis, dactylitis, Patient's Global Assessment of Disease Activity score (PtGA), Psoriatic Arthritis Impact of Disease (PsAID) tool, pain, and pruritus. The current analysis is based on observed data through 1 year of study duration. Results: A total of 545 German patients were enrolled and followed up to 12 months of APR treatment; 488 patients were included in the safety analysis and 418 in the full analysis set. The mean age was 55 years, mean body mass index was 29.5 kg/m 2, and 60% were female. The mean duration of psoriasis and PsA was 26 years and 18 years, respectively. At BL, 46.7% of patients had enthesitis based on the Leeds Enthesitis Index (LEI; mean [SD]: 2.9 [1.72]) and 23% had dactylitis (mean [SD]: 2.2±2.03); 74% of patients were biologic-naive. Effectiveness is shown after ~1 month (Visit 1 [V1]) and ~4 months (Visit 2 [V2]) and for up to 225 patients after 12 months (Visit 5 [V5]) of treatment (Table). Improvements were also seen in PtGA, overall pain, and pruritus. A subanalysis suggests APR was associated with greater benefits in biologic-naive patients compared with patients who previously received biologic therapy. Observed safety and tolerability through V5 were consistent with the known overall safety profile of APR. Common adverse events in clinical trials were similar, with a lower incidence of diarrhea (11.1%), nausea (7.0%), headache (3.9%), and respiratory tract infection (0.8%). Conclusion: Data from this large, real-world cohort of patients with PsA show the effectiveness of APR. In patients with up to 12 months of follow-up, APR was associated with rapid and maintained improvements in physician-assessed and patient-reported outcomes. Safety and tolerability were consistent with the known profile of APR. Disclosure of Interests: Jürgen Wollenhaupt Grant/research support from: Abbott, BMS, MSD, Pfizer, UCB – grant/research support, Consultant of: Abbott, BMS, MSD, Pfizer, UCB – consultant, Harald Strothmeyer: None declared, Michael Fiene: None declared, Stephan Morys Employee of: Amgen Inc. – employment; Celgene GmbH – employment at the time of study conduct, Christian Bach Employee of: Amgen Inc. – employment; Celgene GmbH – employment at the time of study conduct, Josefine Roemmler-Zehrer Employee of: Amgen Inc. – employment; Celgene GmbH – employment at the time of study conduct